2014
DOI: 10.1021/am503997e
|View full text |Cite
|
Sign up to set email alerts
|

Sandwichlike Magnesium Silicate/Reduced Graphene Oxide Nanocomposite for Enhanced Pb2+ and Methylene Blue Adsorption

Abstract: A sandwichlike magnesium silicate/reduced graphene oxide nanocomposite (MgSi/RGO) with high adsorption efficiency of organic dye and lead ion was synthesized by a hydrothermal approach. MgSi nanopetals were formed in situ on both sides of RGO sheets. The nanocomposite with good dispersion of nanopetals exhibits a high specific surface area of 450 m(2)/g and a good mass transportation property. Compared to MgSi and RGO, the mechanical stability and adsorption capacity of the nanocomposite is significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
102
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(108 citation statements)
references
References 45 publications
6
102
0
Order By: Relevance
“…A remarkable maximum adsorption capacity of 1603 mg g − 1 was obtained at pH = 10, which is much larger than absorption capacities of b-MB reported for adsorbents such as carboxylic acid-functionalized mesoporous silica (159 mg g − 1 ) 26 and activated carbon (400-600 mg g − 1 ), 24 as well as reduced graphene oxide nanocomposite (433 mg g − 1 ). 27 The plot of lnQ e versus lnC e for b-MB is given in Supplementary Figures S2c and d, and the Freundlich Multilevel structured porous polymer particles as super-adsorbent materials D Chen et al constant K F ((mg g − 1 ) × (l mg − 1 ) 1/n ) and the heterogeneity factor (1/n) is presented in Table 1. The results shown in Supplementary Figure S2 and Table 1 reveal that the fitting degree of the Freundlich model was slightly lower than that of the Langmuir model (correlation coefficient o0.95).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable maximum adsorption capacity of 1603 mg g − 1 was obtained at pH = 10, which is much larger than absorption capacities of b-MB reported for adsorbents such as carboxylic acid-functionalized mesoporous silica (159 mg g − 1 ) 26 and activated carbon (400-600 mg g − 1 ), 24 as well as reduced graphene oxide nanocomposite (433 mg g − 1 ). 27 The plot of lnQ e versus lnC e for b-MB is given in Supplementary Figures S2c and d, and the Freundlich Multilevel structured porous polymer particles as super-adsorbent materials D Chen et al constant K F ((mg g − 1 ) × (l mg − 1 ) 1/n ) and the heterogeneity factor (1/n) is presented in Table 1. The results shown in Supplementary Figure S2 and Table 1 reveal that the fitting degree of the Freundlich model was slightly lower than that of the Langmuir model (correlation coefficient o0.95).…”
Section: Resultsmentioning
confidence: 99%
“…22 Pollutant remediation via adsorption processes is considered to be one of the most promising techniques owing to operation simplicity, high efficiency and applicability for the treatment of wastewater on a large scale. 23 In addition to the traditional activated carbon, 24 different types of adsorbent materials have been developed, such as natural or synthetic zeolites, 25 organically modified porous silica, 26 natural or modified clays 27 and macroporous polymeric adsorbents. 28 However, inherent drawbacks for such materials include high operation costs, long time consumption, low selectivity, limited adsorption capacities and difficulties in their regeneration and reuse.…”
Section: Introductionmentioning
confidence: 99%
“…S2b, Supplementary Information). At the moderate pH value of 11.9, the dissolution of PAL and associated minerals and the formation of magnesium silicates simultaneously occurred, which is favorable to the uniform growth of the Mg-silicate to form spherical particles3839. After hydrothermal reaction, the pH value of Si/Mg ratio at 2:1 was tested to be 11.8 (11.9 before reaction), indicating that constant alkaline condition is important for the formation of the spherical particles.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in recent years, great concerns have been paid on the hybrid materials with nano/micro structure3233 and the mesoporous materials with excellent performance343536. Hydrothermal process has been used to synthesize various metal silicate hybrid materials with different morphologies, porous structure and superior adsorption performance373839. It has been demonstrated that the new metal silicates could be synthesized by a hydrothermal process using PAL clays as Si, Mg and Al sources without considering their grade.…”
mentioning
confidence: 99%
“…Since dyes existed in industrial effluents are toxic to microorganisms and can impede the photosynthesis of aqueous flora, the ecological balance may be destroyed ultimately [5,6]. What is worse, dyes can also threaten human health by polluting river and groundwater [7]. As a result, it is necessary to treat these industrial effluents before discharge.…”
Section: Introductionmentioning
confidence: 99%